Proceedings of the 2019 AAAI/ACM Conference on AI, Ethics, and Society 2019
DOI: 10.1145/3306618.3314288
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate Feedback Loops in Recommender Systems

Abstract: Machine learning is used extensively in recommender systems deployed in products. The decisions made by these systems can influence user beliefs and preferences which in turn affect the feedback the learning system receives -thus creating a feedback loop. This phenomenon can give rise to the so-called "echo chambers" or "filter bubbles" that have user and societal implications. In this paper, we provide a novel theoretical analysis that examines both the role of user dynamics and the behavior of recommender sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 18 publications
0
111
0
1
Order By: Relevance
“…Despite the reasonableness of prior works, severe limitations do exist, making the claims only plausible. One major aspect is that most of the existing works draw conclusions by means of simulation, or relying on some self-defined networks and measurements with simplified dynamics [6,9,15,20,26,31]. Building upon the subjective assumptions, whether the modeling and analysis have the capability to reflect the truth seems to be dubious [37].…”
Section: Related Workmentioning
confidence: 99%
“…Despite the reasonableness of prior works, severe limitations do exist, making the claims only plausible. One major aspect is that most of the existing works draw conclusions by means of simulation, or relying on some self-defined networks and measurements with simplified dynamics [6,9,15,20,26,31]. Building upon the subjective assumptions, whether the modeling and analysis have the capability to reflect the truth seems to be dubious [37].…”
Section: Related Workmentioning
confidence: 99%
“…AI can play multiple roles in a system, from being an element, such as teaching robots used in primary schools (Breazeal 2019). It could also play a role as an organizing force, as many people experience when using social media such as Google Maps and Facebook, or in self-reinforcing feedback loops facilitating the achievement of something, such as Amazon or YouTube's recommender systems designed to change behavior patterns (Jiang et al 2019).…”
Section: Systems-based Approachmentioning
confidence: 99%
“…Some methods use post learning techniques which consist of different ranking and arXiv:2001.04832v1 [cs.IR] 1 Jan 2020 selection strategies after performing the predictions. In this family, we find a big interest in Multi-Armed Bandit techniques [12] since they have proven to be efficient in the exploitation vs exploration problems [13]. MAB are good with exploration problems, they are often used in Recommender systems in order to solve the exposure bias problem.…”
Section: Related Workmentioning
confidence: 99%
“…MAB are good with exploration problems, they are often used in Recommender systems in order to solve the exposure bias problem. For instance, a group of DeepMind researchers [12] have recently used MAB to study the effect of the feedback loop in recommender systems. They showed that the feedback loop can decrease the quality of the recommendations and they also showed that random exploration using Multi-Armed Bandit techniques can enhance and boost the quality of the predictions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation